Chrysis subcoriacea Linsenmaier 1959 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
51. Chrysis subcoriacea Linsenmaier, 1959 Chrysis longula subcoriacea Linsenmaier 1959: 160. Holotype ♀; Finland: Kyrkslätt [= Kirkkonummi] (NMLS) (examined). Chrysis subcoriacea : Valkeila 1962: 64, Erlandsson 1971: 90, Silfverberg 1981: 61, Vikberg 1986b: 68, Söderman & Vikberg 2003: 45, Soon 2004: 24, 46, Sörensson 2008a: 80, Franzén & Norén 2009: 40, Johansson 2010: 118, Orlovskytė et al. 2010: 152, Paukkunen 2010: 538, Ivarsson 2011: 43, Larsson 2012: 12, Ranta 2012: 33, Rosa & Soon 2012, Johansson 2013a: 81, Johansson 2013b: 21, Dyntaxa 2013, Soon et al. 2014: 304, 318. Chrysis longula [part.]: Kimsey & Bohart 1991: 434. Material examined. Denmark: EJ : Virklund, 2.V.1944, 2 ♂♂; NWJ : Thy, ’Nors Øregård’, 16.VI.1953, 1 ♀ (Ardö); SJ : Stensbaek plantage, 20.VI.1949, 1♀ (Worm-Hansen). * Latvia: Ķemeri, 21.VIII.1970, 1 ♀ (V. Tumšs); Ropaži, 5.VI.1966, 1 ♀ (V. Tumšs); Zabludovka, 27.VI.1967, 1 ♀ (V. Tumšs). Norway: BØ : Øvre Eiker, Lilleby, 6.V.2012, 1 ♂; Nedre Eiker, Solbergfjell, 28.VI.2012, 1 ♂ (F. Ødegaard); ON : Nord-Fron, 30.VII–1.IX.2009 1 ♀ (F. Ødegaard). * Russian Fennoscandia (total 11 exx.): Ik : Muolaa [= Pravdino]; Rautu [= Sosnovo]; Terijoki [= Zelenogorsk]; Ka : Seiskari [= Ostrov Seskar]; Viipuri [= Vyborg]; Kol : Petrozavodsk. Distribution. Denmark, Estonia, Finland, * Latvia, Norway, Sweden, *Russian Fennoscandia.—Transpalearctic: from central and northern Europe to central Asia and Japan (Linsenmaier 1997). Linsenmaier’s (1997) record from Svalbard is based on a specimen collected from ”W. Spitzbergen, Richerche Bay” in 16th of July during A.G. Nathorst's expedition of 1898. The specimen is deposited in Linsenmaier’s collection, Luzern, and most likely it is the northernmost cuckoo wasp ever collected. However, the specimen must have been accidentally imported into the area, as no host species are known to occur on Svalbard, and it is unlikely that it could have flown there by itself. Remarks. The species has been found from all the Nordic and Baltic countries except ...